THE EFFECT OF TRANSACTION COST ECONOMICS ON HYBRID CORN FARMING INCOME IN CIHAUR VILLAGE MAJA SUBDISTRICT MAJALENGKA REGENCY - Zumi Saidah; Lucyana Trimo; Eliana Wulandari; Vina Rachmadina (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Transaction costs on corn farming can affect the income of corn farming. This research aimed to identify the transaction cost economics (TCE) structure and analyze the effect of TCE on the income of hybrid corn farming. The research method used is TCE analysis and multiple linear regression analysis. This research was conducted in Cihaur Village, Maja Subdistrict, Majalengka Regency, West Java, on 64 respondents. The research results showed that the transaction cost economics component on hybrid corn farming consists of (1) information cost; (2) negotiation cost; (3) coordination cost; (4) implementation cost; and (5) risk cost. The amount of the transaction cost that is formed on hybrid corn farming was Rp105,421.16. The percentage of transaction cost to total production cost was 2,78%. Coordination costs consisted of meeting cost, and farmer group fees have the highest transaction costs component, leading to 41,96%. On the other hand, risk cost has the lowest prices, merely 3,09%, in which there are avoiding risk cost and controlling risk cost. The results showed that the seven variables tested had significant effects on the income of corn farming. These variables included land area, fertilizer costs, seed costs, selling price, labor wages, productivity, and transaction cost. Keywords: income, farming, hybrid corn, production cost, transaction cost